Experiments of transpiration cooling inspired panel cooling on a turbine blade yielding film effectiveness levels over 95% - Wambersie, A; Wong, H; Ireland, P; Mayo, I (MDPI, 2021)
Panels were tested at different locations around the turbine blade, on both suction and pressure surfaces. Three different surface porosities were also tested. Results demonstrated that the approach can be very successful with high levels of film cooling effectiveness, exceeding 95%, achieved using low coolant mass flow rates. Increasing the surface porosity also proved to be an important parameter in the panel’s performance. Additionally, staggering the film holes lead to significant positive interactions between individual films, resulting in much improved panel performance.